Cytotoxicity Assay of Water, Ethanol N-Hexane Extract of Dates Fruit (Phoenix dactylifera) Against Murine Leukemia Cancer Cell P388 - Lilis Febriyanti; Yayat Sudaryat (Syntax Literate, 2021)
The World Health Organization (WHO) states, in 2015, there are an estimated 9 million people who die of cancer and in 2030 there are an estimated 11.4 million deaths from cancer. Blood cancer reaches 3% of all cancers found in humans and is most common in children. The cancer drug that is available today has quite severe side effects, therefore in this study an antileukemia activity test will be carried out on water, 70% ethanol, and n-hexane extract of dates (Phoenix dactylifera). This study, the extracts from dates will be tested for cytotoxicity on Murine Leukemia P388 cells using the MTT Assay method. The IC50 value of extract of dates is used as an assessment of the activity of palm fruit extract as antileukemia. Citotoxicity assay against Murine Leukemia P388 cells by MTT assay, showed IC50 value is more than 100 Âµg/mL for all extracts. This result informed that the water, ethanol, and n-hexane extract of dates fruit are less potencial as a antileukemia agent.